2014
DOI: 10.1155/2014/675212
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nursing Process and Its Affecting Factors among Nurses Working in Mekelle Zone Hospitals, Northern Ethiopia

Abstract: Background. Nursing process is considered as appropriate method to explain the nursing essence, its scientific bases, technologies and humanist assumptions that encourage critical thinking and creativity, and permits solving problems in professional practice. Objective. To assess the application of nursing process and it's affecting factors in Mekelle Zone Hospitals. Methods. A cross sectional design employing quantitative and qualitative methods was conducted in Mekelle zone hospitals March 2011. Qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
3
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 9 publications
10
101
3
12
Order By: Relevance
“…"The nursing process is an important part of the day-to-day work of nurses because it enables nurses to achieve effective care and improve the quality of care", "... the nursing process is an essential place ...", "... a key place...", "... a key and priority place ...". Our results are consistent with those of Aiyedun in Abuja [2], who found that 69% of nurses believe that quality nursing care cannot be achieved without the nursing process, and Ethiopia, where 88% of nurses said that the process of nursing helps provide quality nursing care [8].…”
Section: Discussionsupporting
confidence: 91%
“…"The nursing process is an important part of the day-to-day work of nurses because it enables nurses to achieve effective care and improve the quality of care", "... the nursing process is an essential place ...", "... a key place...", "... a key and priority place ...". Our results are consistent with those of Aiyedun in Abuja [2], who found that 69% of nurses believe that quality nursing care cannot be achieved without the nursing process, and Ethiopia, where 88% of nurses said that the process of nursing helps provide quality nursing care [8].…”
Section: Discussionsupporting
confidence: 91%
“…It is in the midst of efforts for this recognition that SNC cannot be understood as a "ready prescription", and it is necessary for the team to understand the importance of structured permanent education in order to understand the process as critical and reflective knowledge for care. 9,14,[18][19] Regarding nurses' knowledge about NP as an instrument of the Systematization of Nursing Care in the Human Milk Bank, the stages of this instrument are unique and deserve to be observed. The first stage of the NC, the nursing data collection, also known as a nursing history and investigation, is described as a deliberate, systematic and continuous process, carried out with the aid of varied methods and techniques, whose purpose is to obtain information about the person, family or community and their responses at a given moment in the health and disease process.…”
Section: 11mentioning
confidence: 99%
“…3,4,7 It is known that nursing technicians are important in this process, as they should participate in the implementation of the care plan, together with the nurse, considering that everyone can contribute, at the appropriate time, with information or activities that favor the care for the patient. 4 However, it is known that the training process of nursing technicians presents a deficit regarding NCS, with this issue often only included in the training of higher level professionals.…”
Section: 3mentioning
confidence: 99%
“…3 Similarly, a study aiming to comprehend the interactional planning-implementation process of NCS in a university hospital in São Paulo state, found that the professionals did not legitimize NCS in their work environment, due to the NCS implementation process not having favorable conditions for the success of the proposal.…”
Section: I'm Aware Of the Importance Of The Participation Of Nursing mentioning
confidence: 99%